Architecture as Place Making: a Sustainable Farmstead and Staff Housing - Steven Downen; Stanley Koehn; Douglas Pierce; Daryl Rantis (Oz, 1986)
A growing number of architects are becoming aware of the necessity to design with respect and response to the natural ecosystem. The advent of environmental criteria in architecture is part of a burgeoning realization that industrial societies are not environmentally sustainable...